Boundary Traceability Conditions in Food Supply Chains Using Block Chain Technology - Samal, Ansuman; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
Traceability of food supply chains products has become crucial in an environment in which economies are becoming competitive, heterogeneous and diverse and in which consumers expect high quality. The food supply chain is made up of many organizations with different interests, and is often reluctant to share information on traceability with each other. By establishing transparency, Block chain has been promoted to enhance traceability. Practice therefore appeared to be more persistent. The purpose of this paper is to define the boundary conditions for sharing information regarding assurance in order to improve traceability. Four cases were investigated using a template analysis of 16 interviews in the food supply chain. Eighteen boundary requirements were established, classified in the categories industry, policy, efficiency and traceability. Some boundary conditions were found in all supply chains while others were found to be specific to the supply chain. Standardization of traceability processes and interfaces, a joint platform and independent governance have been identified as key boundary conditions before the use of block chain. Our findings imply that supply chain systems need to be modified first and organizational measures need to be taken to meet the boundary conditions before the successful use of block chain can be achieved.